Role of CFTR in Epithelial Differentiation by Functional Genomics - Sousa, Luís Miguel dos Santos (2021)
Cystic Fibrosis (CF) is caused by mutations in the CFTR gene. The relationship between CFTR and differentiation has been firmly documented. However, the mechanisms that regulate this relationship are still unclear. The aim of this work was to further characterize the differentiation defect in CF and to identify the underlying molecular mechanisms. In the first chapter, our results show that CF cells display increased proliferation, acquire lower levels of TEER upon polarization, display slower wound healing, and have altered differentiation. Moreover, our data suggest that partial epithelial-mesenchymal transition occurs in CF cells. Given that Krüppel-like factors (KLFs) play pivotal roles in the regulation of differentiation, in the second chapter we tested the levels of KLF2, 4 and 5 and found that only KLF4 is differentially expressed in CF vs non-CF cells. Therefore, we then assessed whether KLF4 modulation had an impact in CFTR levels and function. Our data show that KLF4 acts as a negative regulator of wt-CFTR expression and function. Noteworthy, F508del cells are relatively insensitive to KLF4 modulation. Next, we tested possible pathways by which KLF4 action can impact CFTR in the CF and non-CF contexts. Our data showed that AKT signalling acts as a modulator of CFTR in a KLF4-dependent way, whilst GSK3β was observed to be a negative regulator of CFTR independent of KLF4 in CF cells. In chapter three, our data show that KLF4 knock-out has no major impact in proliferation but modulates TEER acquisition, wound healing, and differentiation markers differentially in CF vs non-CF cells. Moreover, we characterized the levels of KLFs, CFTR and proteins of interest during epithelial differentiation and showed that maximum KLF4 expression occurs prior to maximum CFTR expression. Altogether these data contribute to mechanistic clarification of the relationship between CFTR and epithelial differentiation.